CPTU-Based Offshore Wind Monopile Rigid Bearing Mechanism Analysis - Jie Zhou; Renjie Gu; Panpan Shen; Chengjun Liu; Zeyao Li; Kefan Zhu; Zhenming Shi (Journal of Marine Science and Engineering)
With the development of the offshore wind industry in China, the amount of offshore wind turbines has increased rapidly. Large-diameter steel monopile foundations of offshore wind turbines have been widely adopted in China with lots of marine clay located. However, the conventional offshore wind monopile bearing capacity prediction from the American Petroleum Institute (API) based on the small-diameter flexible pile field test is inaccurate with the rigid mechanism of large-diameter monopile causing economically loss. The piezocone penetration test (CPTU) is a common marine in situ test to exactly acquire soil parameters. Therefore, a CPTU-based offshore wind monopile rigid mechanism inference method is proposed. A creative numerical offshore wind power monopile and CPTU combined model is established through COMSOL. A self-compiling parameter function is applied to soil modeling and an innovative mobile boundary function is created to simulate CPTU penetration. Through the model, real-time CPTU data can be acquired when monopile is applied with different horizontal loads. The peripile soil stress change can be timely detected by CPTU. Through CPTU data, the monopile rigid bearing mechanism is verified. A rigid rotation center is found at the 60% point of the inserted monopile. The method is an important foundation for the next step of monopile bearing capacity research.